Why Deep Plane Face and Neck Lifting Results in the Maximum Short- and Long-term Results? My Primary Choice for Rhytidectomy in My Practice - Batniji, Rami K. (Facial Plastic Surgery, 2024)
I converted to the extended deep plane facelift and neck lift with a shorter skin flap elevation in the face to achieve a more complete release of the facial ligaments to obtain more mobilization of the skin/superficial musculoaponeurotic system composite flap, and a more medial suspension resulting in improved correction of the midface, nasolabial fold, marionette fold and jowl. Treatment of the deep neck structures allowed for more refinement of the submentum in the deep neck lift procedures as well. In this article, we shall review the surgical technique of the deep plane facelift and neck lift as well as postoperative management pearls, the management of complications from the procedure, and the incorporation of ancillary procedures.
Keywords: neck lift; extended deep plane facelift; rhytidectomy